Effects of anti-beta 2-glycoprotein 1 antibodies and its association with pregnancy-related morbidity in antiphospholipid syndrome (2022)
ABSTRACT: Antiphospholipid syndrome (APS) is an autoimmune disease characterized by venous, arterial, or small-vessel thrombosis and/or pregnancy-related morbidity, associated with persistent positivity of antiphospholipid antibodies (aPL). Pregnancy-related morbidity in APS patients is characterized by unexplained fetal deaths, premature birth of morphologically normal newborns, and/or consecutive pregnancy losses before the 10th week of gestation. Beta 2-glycoprotein 1 (ß2GP1) is the main antigen recognized by aPL and plays an essential role in the pathogenesis of APS. Antibodies against ß2GP1 (aß2GP1) are involved in damage-generating mechanisms in APS due to their interaction with trophoblasts, decidua, and endothelial cells. aß2GP1 might be used as a prognostic tool for obstetric risk stratification and ß2GP1 could be a target for molecular-targeted treatment to prevent pregnancy morbidity in APS. This review describes these aspects of aß2GP1, including effects on different cellular targets, its association with the severity of obstetric manifestations and the potential of ß2GP1-targeted therapies for APS.